Prevalence of peptic ulcer in India: an endoscopic and epidemiological study in urban Kashmir. Issue 7 (July 1989) - Khuroo, M S; Mahajan, R; Zargar, S A; Javid, G; Munshi, S
Abstract : The prevalence of peptic ulcer disease in the general population of Kashmir, India, was determined by endoscopy in a randomly selected sample population of 2763 adults aged 15 years and above who were interviewed using a questionnaire. Of 239 persons with ulcer symptoms, 193 (80.7%) had an oesophagogastroduodenoscopy. A randomly selected 177 individuals from among the remaining population without ulcer symptoms, were also endoscoped. The point prevalence of peptic ulcer was 4.72% and the lifetime prevalence was 11.22%. The duodenal to gastric ulcer ratio was 17.1:1. Duodenal and gastric ulcer were common in men. The prevalence of peptic ulcer increased with age, with a peak prevalence of 28.8% in the 5th decade of life. Peptic ulcer was not related to socio-economic status. The prevalence of complications, such as bleeding, stenosis, or perforation were similar to those reported in the West.